Statistical Analysis of Isothermal Cold Starts of PEFCs: Impact of Gas Diffusion Layer Properties. Issue 10 (1st January 2016) - Biesdorf, Johannes; Forner-Cuenca, A.; Siegwart, M.; Schmidt, T. J.; Boillat, Pierre
Abstract : In this paper, we present experimental results about the influence of a hydrophobic coating of gas diffusion layers (GDL) and the existence of a micro porous layer (MPL) on the cold start capability of Polymer Electrolyte Fuel Cells (PEFC). The experiments were performed on five different cell configurations with an active area of 1 cm 2 including GDLs of 0, 5, 20 wt% PTFE with and without MPL. Two different experiments were realized: First, a statistical analysis of more than 700 isothermal cold starts was performed to analyze the stochastic freezing behavior of supercooled water inside the fuel cells. Second, a certain number of cold starts were investigated with high-resolution neutron radiography in order to understand the implications of the water distribution on the freezing mechanism. Especially at low coating loads, it was found that cell-to-cell variations are more dominant than variations of the materials. In contrast, a significantly reduced variability between the individual cells as well as a general reduction of the probability of cell failure was observed at high coating loads. The observed effects can be mainly explained by changed morphology of the investigated materials. Regarding the existence of an MPL, only minor effects were observed which could be assigned to a different local distribution of water in the porous layers.